Visualizing Vpr-induced G2 arrest and apoptosis. - Tomoyuki Murakami; Yoko Aida (PLoS ONE, 2014)
Vpr is an accessory protein of human immunodeficiency virus type 1 (HIV-1) with multiple functions. The induction of G2 arrest by Vpr plays a particularly important role in efficient viral replication because the transcriptional activity of the HIV-1 long terminal repeat is most active in G2 phase. The regulation of apoptosis by Vpr is also important for immune suppression and pathogenesis during HIV infection. However, it is not known whether Vpr-induced apoptosis depends on the ability of Vpr to induce G2 arrest, and the dynamics of Vpr-induced G2 arrest and apoptosis have not been visualized. We performed time-lapse imaging to examine the temporal relationship between Vpr-induced G2 arrest and apoptosis using HeLa cells containing the fluorescent ubiquitination-based cell cycle indicator2 (Fucci2). The dynamics of G2 arrest and subsequent long-term mitotic cell rounding in cells transfected with the Vpr-expression vector were visualized. These cells underwent nuclear mis-segregation after prolonged mitotic processes and then entered G1 phase. Some cells subsequently displayed evidence of apoptosis after prolonged mitotic processes and nuclear mis-segregation. Interestingly, Vpr-induced apoptosis was seldom observed in S or G2 phase. Likewise, visualization of synchronized HeLa/Fucci2 cells infected with an adenoviral vector expressing Vpr clearly showed that Vpr arrests the cell cycle at G2 phase, but does not induce apoptosis at S or G2 phase. Furthermore, time-lapse imaging of HeLa/Fucci2 cells expressing SCAT3.1, a caspase-3-sensitive fusion protein, clearly demonstrated that Vpr induces caspase-3-dependent apoptosis. Finally, to examine whether the effects of Vpr on G2 arrest and apoptosis were reversible, we performed live-cell imaging of a destabilizing domain fusion Vpr, which enabled rapid stabilization and destabilization by Shield1. The effects of Vpr on G2 arrest and subsequent apoptosis were reversible. This study is the first to characterize the dynamics of the morphological changes that occur during Vpr-induced G2 arrest and apoptosis.